Efficacy of Rupatadine in Treatment of Chronic Idiopathic Urticaria (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Urticaria is a vascular lesion of the skin characterized by the appearance of well demarcated wheels along with angioedema. In more than 75% of cases, a causative agent can’t be established and thus is termed as chronic Idiopathic Urticaria. Treatment of this condition focuses on measures which provide symptomatic relief; 2nd and 3rd generation anti-histaminic drugs are the mainstays now for the treatment of chronic idiopathic urticaria.Objectives: To determine the efficacy of rupatadine in the treatment of chronic idiopathic urticaria.Materials and Methods: A clinical trial was conducted on 60 patients who were suffering from chronic idiopathic urticaria from March to August 2015 at Department of Dermatology and Venereology, Combined Military Hospital (CMH), Dhaka. Tab. Rupatadine 5 mg 1 tab daily was given for 6 weeks. Clinical response of treatment and adverse effect was assessed at every two weeks’ interval by taking history and clinical examination. Ethical issue was addressedResults: The patients reported a considerable improvement in overall chronic idiopathic urticaria due to the use of Rupatadine. The mean total symptom score (TSS) value reduced by 83% compared to the base line evaluation at the end of the therapy duration. Total disappearance of symptom was recorded in 25% patients. There were 79% decrease in the score for number of wheals, 81% reduction in the score for size of the wheals, 88% reduction in the pruritus severity score, and 83% reduction in the duration of pruritus score in relation to baseline evaluation.Conclusion: 5mg of Rupatadine once daily is effective in patients with chronic idiopathic urticaria.JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 39-42